2021
DOI: 10.1021/acssuschemeng.1c01499
|View full text |Cite
|
Sign up to set email alerts
|

New Greener and Sustainable Methodology for Direct Sequestering and Analysis of Uranium Using a Maline Supramolecular Scaffold and Mechanistic Understanding through Speciation and Interaction Studies

Abstract: Research, based on the development of an economical innovative green technology, is the quintessential requirement for the advancement of the nuclear fuel cycle (NFC). The present studies show that Maline, with a preorganized supramolecular scaffold, would be considered as the workhorse for its potential efficacy in diverse facets of the NFC, specifically as an elegant metal hijacker for processing of uranium (U) matrices, designer solvent for green analysis of U, and a promising U chelator for a greener alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…On the other hand, carbide matrices are refluxed in the nitric acid–sulfuric acid mixture to destroy any in situ generated organic acid. In the quest to develop sustainable alternative to hydrometallurgical routes for actinide dissolution, RTIL, DES, and other green solvent-based routes are being explored fervently. , Nevertheless, the extent of “greenness” of various RTILs remains an unanswered question. Also, low thermal stability and high viscosity of DESs pose a challenge for routine operations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, carbide matrices are refluxed in the nitric acid–sulfuric acid mixture to destroy any in situ generated organic acid. In the quest to develop sustainable alternative to hydrometallurgical routes for actinide dissolution, RTIL, DES, and other green solvent-based routes are being explored fervently. , Nevertheless, the extent of “greenness” of various RTILs remains an unanswered question. Also, low thermal stability and high viscosity of DESs pose a challenge for routine operations.…”
Section: Resultsmentioning
confidence: 99%
“…The U�O stretching frequency appeared at 950 cm −1 for UO 2 dissolved in MSA, suggesting the formation of UO 2 2+ kind of species in MSA. 26 From Figure 4a, it was observed that the absorption at 1680 and 3250 cm −1 corresponding to H−O−H bending and O−H stretching modes of water became more prominent for UO 2 dissolved in MSA than for neat MSA.…”
Section: Probing Redox Speciation and Complexationmentioning
confidence: 96%
“…Kinetics of dissolution in this neutral DES was better that that of HDEHP in IL [21] and [DMAH][NTf 2 ]. [15] Even, dissolution time was much shorter than that of Maline [18] and PTSA/ChCl DESs. [12] To determine the solubility of UO 3 in this DES, we added higher amount (300 mg) of UO 3 into 2 mL of DES and stirred at 80 °C.…”
Section: Dissolution Of Uranium Oxides In Synthesized Desmentioning
confidence: 96%
“…It has been reported that dissolution of UO 2 and U 3 O 8 occurs via oxidation of U 4 + to U 6 + in ILs and DESs. [18,29] In this DES due to the hydrophobic nature as well as due to the absence of oxidizing agent, the oxidation reaction is hindered. Hence, UO 3 is dissolved while UO 2 and U 3 O 8 remain insoluble.…”
Section: Dissolution Of Uranium Oxides In Synthesized Desmentioning
confidence: 99%
See 1 more Smart Citation